Whose Opinions Count in Educational Policymaking? - Joel Malin; Christopher Lubienski (Arizona State University, 2013)
The success of some advocacy organizations in advancing their preferred policies despite questionable evidence of the effectiveness of these policies raises questions about what contributes to successful policy promotion.  We hypothesize that some education-focused organizations are advancing their agendas by engaging media, with individuals who may not possess traditionally defined educational expertise. Using two distinct expert lists, we examined relationships between measures of expertise and educational impact.  We found non-significant positive relationships between these measures with a list of experts complied by a conservative think tank, while a second list from a university-based center showed a significant positive relationship. We conclude that media impact is at best loosely coupled to expertise.  This issue should be explored in greater depth because deleterious outcomes are more likely if individuals are more successful in shaping policy discussion based on criteria outside of expertise.